Positive Prerequisites for the Use of Reliefs in the Payment of Dues on Social Insurance Contributions - Zbigniew Ofiarski (Prawo Budżetowe Państwa i Samorządu)
It is permissible to use reliefs in the payment of social security contributions, based either on a definitive waiver by the creditor of the whole or relevant part of the amount due (partial or complete remission) or only a temporary waiver of such amounts (payment deferral or payment in installments). The use of such reliefs is possible upon the occurrence of conditions laid down in the Act, for example, in the case of total non-recovery of contributions, for economic or other reasons worth considering, if justified by important interests of the person concerned. The prerequisites mentioned above have a nature of general clauses, allowing for their flexible adjustment to specific situations. Entities authorized to grant reliefs in the payment of social security contributions act within the limits of administrative discretion. But it is not a fully free operation, because the economic impact resulting from the use of such reliefs has a direct impact on the financial balance of earmarked funds which finance social security benefits, in particular pensions, disability allowances and other benefits.